2012
DOI: 10.1016/j.orgel.2012.03.007
|View full text |Cite
|
Sign up to set email alerts
|

A graph-based formulation for computational characterization of bulk heterojunction morphology

Abstract: Organic solar cells (OSC) have the potential for widespread usage, due to their promise of low cost, roll-to-roll manufacturability, and mechanical flexibility. However, ubiquitous deployment is impeded by their relatively low power conversion efficiencies (PCE). The last decade has seen significant progress in enhancing the PCE of these devices through various strategies. One such approach is based on morphology control. This is because morphology affects all phenomena involved in solar conversion: (1) light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 52 publications
0
79
0
Order By: Relevance
“…Additionally, removing assumptions about the differences between inter-and intra-chain transport and carrier delocalization by instead using QCCs to determine the electronic couplings between small chromophores in-situ, the quantitative discrepancy between these investigations and experimental data appears to be reduced. Coupling charge transport studies with structural analysis of the electrical network [122,153,154] or crystal packing [80,123], can help predict the morphological features that provide the best device performance. Extending the scope of the KMC simulations beyond the bulk, pristine domain to molecular and electrical interfaces for different materials allows for the prediction of full device performance characteristics such as power conversion efficiencies and J-V curves.…”
Section: Charge Mobilitymentioning
confidence: 99%
“…Additionally, removing assumptions about the differences between inter-and intra-chain transport and carrier delocalization by instead using QCCs to determine the electronic couplings between small chromophores in-situ, the quantitative discrepancy between these investigations and experimental data appears to be reduced. Coupling charge transport studies with structural analysis of the electrical network [122,153,154] or crystal packing [80,123], can help predict the morphological features that provide the best device performance. Extending the scope of the KMC simulations beyond the bulk, pristine domain to molecular and electrical interfaces for different materials allows for the prediction of full device performance characteristics such as power conversion efficiencies and J-V curves.…”
Section: Charge Mobilitymentioning
confidence: 99%
“…Wodo et al presented a graph-based framework to efficiently compute a broad suite of physically morphology descriptors [122]. Two large sets of morphologies with the blend weight ratios of 1:1 and 1:0.82 (A:D) have been employed to study thermal annealing, as shown in Figure 16.…”
Section: Thermal Annealingmentioning
confidence: 99%
“…In this paper, we build on our previous work by analyzing these very complex and convoluted data sets, decomposing them into a set of physically meaningful morphology descriptors 40 by extending our computational framework to account for a three-phase morphology. Specifically, the connectivity of the domains, the distance between domains and electrodes, the domain size distribution, and the tortuosity of charge transport paths are quantified; all in the true three-phase, threedimensional nature of the morphology.…”
Section: Introductionmentioning
confidence: 99%